Assessing seasonal variation of synthetic musks in beach sands from Oporto coastal area: A case study. (July 2017) - Homem, Vera; Magalhães, Inês; Alves, Arminda; Santos, Lúcia
Abstract: Synthetic musk compounds are widely used in the formulation of several cosmetics, personal care and household products. Due to their massive and widespread use, together with some health concerns, they are considered emerging pollutants and have been detected in different environmental compartments. This study focused on the evaluation of the concentration of synthetic musks (five nitro, five polycyclic and one macrocyclic musks) in beach sands, from Oporto coastal area (Portugal), contributing to the enhancement of the knowledge of levels, trends and behaviour of these compounds in this particular matrix. To accomplish this task, a QuEChERS methodology ("Quick, Easy, Cheap, Effective, Rugged, and Safe") coupled to gas chromatography-mass spectrometry (GC-MS) was successfully used to determine synthetic musks from beach sand. The chosen methodology proved to be suitable, achieving satisfactory results for precision (relative standard deviation values below 15%), accuracy (average recovery of 97%) and limits of detection (below 38 pg g −1 ). Synthetic musks were detected in all 45 analysed samples, in concentrations ranging from 0.01 to 27 ng g −1 dw . Tonalide (93%), exaltolide (89%) and galaxolide (76%) were the most commonly detected compounds, but also those detected in higher concentrations (up to 27 ng g −1 dw ). Musk ambrette, moskene, tibetene and xylene were not detected in any of the samples. Higher concentrations were as expected detected in the Summer (total average concentration of 9.21 ng g −1 dw ), namely in samples from Valadares Sul (29 ng g −1 dw ), Francelos (25 ng g −1 dw ) and Castelo do Queijo (25 ng g −1 dw ). The preliminary environmental risk assessment study based on the determination of hazard quotients revealed that the presence of analysed compounds (tonalide, galaxolide and musk ketone) seems to pose no risk to the studied environmental compartment. Graphical abstract: Highlights: First application of QuEChERS extraction to determine synthetic musks in sand. Synthetic musks were detected in all analysed sand samples. Tonalide, exaltolide and galaxolide were the most frequently detected. Higher levels of synthetic musks were detected during the Summer. Abstract : Synthetic musks were detected in beach sands from Oporto coastal area.